101 - HYDRATION AND ALIMENTARY HABITS IN PRÉ-, DURING AND POST-TRAINING OF A MEN'S TEAM HANDBALL UNIVERSITY, RIO DE JANEIRO (Fiep Bulletin - online, 2011)
In collective sports, the appropriate feeding and hydration are fundamental not only in the search of results, but for the warranty of their apprentices' health. This study aimed to describe the hydration and dietary habits in pre, during and post-training of a men's team handball university, Rio de Janeiro. In September 2008, it was realized a descriptive, cross-sectional and with primary base study with fourteen masculine athletes, aged from 19 to 35 years old, volunteers, all belonging to handball masculine team from UNISUAM. A formulary was developed to make athlete's nutritional follow-up, and it was used by students of nutrition both before, during and after training. Data were typed, consolidated and analyzed by the software Excel for Windows 2007, as well as explored by means of absolute and relative frequencies and measures of central tendency (average and standard deviation) from the selected variables. The athletes' average age (years) was 25.6±5.5; average height (m) was 1.79±0.08; and average body weight (Kg) were 81.18±13.2. As for the meal type, it was verified that 86% of the athletes referred to have a snack and 14% to eat lunch before the training, mainly, in the university. As the hydration, was detected that 64.3% of the athletes were hydrated before the physical training, of these 44.4% they drank water, 22.2% orange juice and 22.2% soft drinks. All of the athletes ingested water during and post-training. The conclusion is that the handball athletes need to improve the alimentary choices inside of what it is recommended in the literature. The ingestion of water was adequate during and post-training.
Keywords: Alimentary Habits; Handball; Hydration